Lectotypification of Pyrus astateria Cardot (Rosaceae) - Chen, Xin; Deng, Yunfei (Phytotaxa, 2014)
Sorbus astateria (Cardot) Handel-Mazzetti (1933: 466) was originally described as Pyrus astateria Cardot (1918: 348). When Cardot (1918) described this new species, six collections (Ducloux 114, 3318, 3485, 4115, 4751 and Delavay s.n) from Yunnan, China, were cited in the protologue. According to Art. 9.5 (McNeill et al. 2012), all of these specimens are syntypes. When Aldasoro et al. (2004: 63) revised Sorbus Linnaeus (1753: 477) subgenera Aria Persoon (1806: 39) and Torminaria (Candolle 1825: 636) Koch (1853: 178), they declared that they did not find these specimens at P and therefore designated Sino-Amer. Bot. Exped. 593 (CAS) as a neotype. However, during studies of the Chinese Sorbus, all gatherings cited by Cardot were discovered at P and their images are available on the website of the herbarium (http://coldb.mnhn.fr). Therefore, the neotype chosen by Aldasoro et al. must be superseded under Art.9.19 (McNeill et al., 2012). After examining the specimens cited by Cardot, all were in accordance with the original description. On Ducloux 114, an illustration with an analysis was pasted. Accordingly, we here designate Ducloux 114 as the lectotype.